Bismuth oxide film: a promising room-temperature quantum spin Hall insulator. (16th February 2018) - Wang, Ya-Ping; Li, Sheng-Shi; Ji, Wei-Xiao; Zhang, Chang-Wen; Li, Ping; Wang, Pei-Ji
Abstract: Two-dimensional (2D) bismuth films have attracted extensive attention due to their nontrivial band topology and tunable electronic properties for achieving dissipationless transport devices. The experimental observation of quantum transport properties, however, are rather challenging, limiting their potential application in nanodevices. Here, we predict, based on first-principles calculations, an alternative 2D bismuth oxide, BiO, as an excellent topological insulator (TI), whose intrinsic bulk gap reaches up to 0.28 eV. Its nontrivial topology is confirmed by topological invariant Z 2 and time-reversal symmetry protected helical edge states. The appearance of topological phase is robust against mechanical strain and different levels of oxygen coverage in BiO. Since the BiO is naturally stable against surface oxidization and degradation, these results enrich the topological materials and present an alternative way to design topotronics devices at room temperature.